Data recovery and business continuity in cloud computing: a review of the research literature - Alshammari, Mohammad M.; Alwan, Ali Amer; Taha Alshaikhli, Imad Fakhri (Advanced Institute of Convergence Information Technology Research Center, 2016)
Cloud Computing is an attracting technology in the area of information technology as it carries a number of distinct technologies which have established over time. Disaster Recovery (DR) is a system in which can be used to reduce the actual downtime once software or hardware breakdown. Business Continuity (BC) is an important requirement for the majority of organizations. This paper reviews the research literature on the concepts of cloud computing, disaster recovery, and business continuity. A systematic review carried out of the research dealing with the content of cloud computing, disaster recovery, and business continuity, a literature search was conducted on several electronic databases. Studies published from the years 1995 to 2015 were considered and were selected. This review paper helps the information technology industry to clarify how and have a comprehensive idea about the concepts of cloud computing, disaster recovery, and business continuity and their associated benefits and issues.